2007
DOI: 10.1007/s00382-007-0265-6
|View full text |Cite
|
Sign up to set email alerts
|

Closure of the Panama Seaway during the Pliocene: implications for climate and Northern Hemisphere glaciation

Abstract: The ''Panama Hypothesis'' states that the gradual closure of the Panama Seaway, between 13 million years ago (13 Ma) and 2.6 Ma, led to decreased mixing of Atlantic and Pacific water Masses, the formation of North Atlantic Deep water and strengthening of the Atlantic thermohaline circulation, increased temperatures and evaporation in the North Atlantic, increased precipitation in Northern Hemisphere (NH) high latitudes, culminating in the intensification of Northern Hemisphere Glaciation (NHG) during the Plioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
165
2
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(193 citation statements)
references
References 62 publications
16
165
2
5
Order By: Relevance
“…54). That the closure and associated enhanced MOC is unable to produce large-scale ice sheets in numerical models 55 may be owing to the use of similar to modern boundary conditions (gateways and orography) for the Pliocene. However, adjusting the models for orographic changes over Greenland, and the exposed landmasses of northern Eurasia above a threshold for glacial ice accumulation and massive winter sea ice coverage since ca.…”
Section: Discussionmentioning
confidence: 99%
“…54). That the closure and associated enhanced MOC is unable to produce large-scale ice sheets in numerical models 55 may be owing to the use of similar to modern boundary conditions (gateways and orography) for the Pliocene. However, adjusting the models for orographic changes over Greenland, and the exposed landmasses of northern Eurasia above a threshold for glacial ice accumulation and massive winter sea ice coverage since ca.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the PRISM2 Pliocene HadCM3 model setup and modifications to this configuration to include an open CAS are given by Haywood and Valdes (2004) and Lunt et al (2008), respectively. (Note that Lunt et al, 2008, present their findings in the chronological framework of the CAS closing through time.…”
Section: Messinian Control Configurationmentioning
confidence: 99%
“…Therefore, one change made to the model configuration of Haywood and Valdes (2004) was to open the CAS, as per Lunt et al (2008).…”
Section: Messinian Control Configurationmentioning
confidence: 99%
“…Although many circumstances could have caused cooling between the early and late Pliocene (e.g. Sjunneskog and Winter 2012), it has been shown that the closure of the Panama Seaway during the Pliocene would cool the western Ross Sea region by up to 2°C (Lunt et al 2008). …”
Section: Seasonalitymentioning
confidence: 99%